From plot to watershed management: Experience in farmer participatory Vertisol technology generation and adoption in highland Ethiopia - Jabbar, M.A.; Mamo, T.; Mohamed-Saleem, M.A. (CAB International, 2001)
This chapter summarises the experience of a research project for developing and disseminating technologies for better management of Vertisols for improving productivity. Topics of discussion include Vertisol technology Development and testing in Ethiopia; the adoption pathways for the BBM package at research sites and related factors; factors influencing adoption outside research villages; externality and the need to move from plot to watershed; experience on watershed management; determinants of individual household contributions to drainage construction and current research - from Vertisols management to integrated resource management.